2012
DOI: 10.1242/jcs.094169
|View full text |Cite
|
Sign up to set email alerts
|

Cdt1p, through its interaction with Mcm6p, is required for the formation, nuclear accumulation and chromatin loading of the MCM complex

Abstract: SummaryRegulation of DNA replication initiation is essential for the faithful inheritance of genetic information. Replication initiation is a multi-step process involving many factors including ORC, Cdt1p, Mcm2-7p and other proteins that bind to replication origins to form a pre-replicative complex (pre-RC). As a prerequisite for pre-RC assembly, Cdt1p and the Mcm2-7p heterohexameric complex accumulate in the nucleus in G1 phase in an interdependent manner in budding yeast. However, the nature of this interdep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 48 publications
5
29
0
Order By: Relevance
“…Figure 1a (arrowheads) shows that both Mcm6, as previously shown15, and Mcm2 were co-immunoprecipitated with Cdt1 using an anti-Cdt1 antibody in a Cdt1-dependent manner. We next used glycerol gradients to examine complex formation between Cdt1, Mcm2 and Mcm6 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 71%
“…Figure 1a (arrowheads) shows that both Mcm6, as previously shown15, and Mcm2 were co-immunoprecipitated with Cdt1 using an anti-Cdt1 antibody in a Cdt1-dependent manner. We next used glycerol gradients to examine complex formation between Cdt1, Mcm2 and Mcm6 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 71%
“…7). Consistent with direct interactions between Mcm6 and Cdt1 (Wu et al, 2012), MCM6RA (and to a lesser extent its ATPase site counterpart, MCM2KA) showed reduced recruitment of Cdt1 and Mcm2-7 during OCCM complex formation (Fig. 2 and S2C).…”
Section: Discussionsupporting
confidence: 66%
“…Yeast cell cycle block and release with 5 mg/ml a-factor (G 1 phase), 150 mM hydroxyurea (S phase) or 10-20 mg/ml nocodazole (M phase) at permissive/non-permissive temperatures were carried out as described previously (Wu et al, 2012). Flow cytometry was done as previously described (Zhang et al, 2002).…”
Section: Cell Cycle Synchronization and Flow Cytometrymentioning
confidence: 99%